Sand and grass surfaces are equally effective in promoting positive adaptations in the sprint performance of elite young soccer players - Lucas A. Pereira; Renan Nunes; Tomás Freitas; Carlos Paes; Juan Conde; Luiz Novack; Thiago Kosloski; Rodrigo Silva; Paulo H.S.M. Azevedo; Irineu Loturco (Termedia Publishing House, 2023)
This study compared the effects of two sprint-jump training programmes, performed on either sand or grass surfaces, on the sprint and jump performance of elite young soccer players over an 8-week training period. Fifteen under-20 soccer players were randomly allocated to the sand (n = 7) or grass (n = 8) group. Athletes performed 12 training sessions, comprising vertical and horizontal jump exercises, and linear and change-of-direction (COD) sprint drills. Pre- and post-measurements were completed in the following order: vertical jump, sprint speed at 10 m and 17 m, curve sprint (CS), and modified Zigzag COD tests. Between-group differences were determined using a two-way ANOVA with repeated measures and effect sizes (ES). No improvements in jump performance were found in either group. Significant increases were observed in the sand group for acceleration in 0-10 m and for 10- and 17-m linear sprint velocity (ES = 1.15, 1.16, and 1.81, respectively; P 0.05). Both sand and grass groups revealed similar increases in the CS and COD velocities after the training period (ES ranging from 0.98 to 1.93; P < 0.05). In conclusion, sprint-jump training programmes performed on both grass and sand surfaces elicited significant improvements in CS and COD performances, whereas acceleration and linear sprint velocity increased only in the sand group, after a short-term training period. The sand training surface was proven to be a practical strategy to improve sprint performance in all its forms in soccer players, which is of great interest and importance for coaches and sport scientists working in elite soccer.